Determining possible shared genetic architecture between myopia and primary open-angle glaucoma - Iglesias, AI; Ong, JS; Khawaja, AP; Gharahkhani, P; Tedja, MS; Verhoeven, VJM; Bonnemaijer, PWM; Wolfs, RCW; Young, TL; Jansonius, NM; Craig, JE; Stambolian, D; et al. (Association for Research in Vision and Ophthalmology, 2019)
Purpose:To determine genetic correlations between common myopia and primary open-angle glaucoma (POAG). Methods:We tested the association of myopia polygenic risk scores (PRSs) with POAG and POAG endophenotypes using two studies: the Australian & New Zealand Registry of Advanced Glaucoma (ANZRAG) study comprising 798 POAG cases with 1992 controls, and the Rotterdam Study (RS), a population-based study with 11,097 participants, in which intraocular pressure (IOP) and optic disc parameter measurements were catalogued. PRSs were derived from genome-wide association study meta-analyses conducted by the Consortium for Refractive Error and Myopia (CREAM) and 23andMe. In total, 12 PRSs were constructed and tested. Further, we explored the genetic correlation between myopia, POAG, and POAG endophenotypes by using the linkage disequilibrium score regression (LDSC) method. Results:We did not find significant evidence for an association between PRS of myopia with POAG (P = 0.81), IOP (P = 0.07), vertical cup-disc ratio (P = 0.42), or cup area (P = 0.25). We observed a nominal association with retinal nerve fiber layer (P = 7.7 × 10-3) and a significant association between PRS for myopia and disc area (P = 1.59 × 10-9). Using the LDSC method, we found a genetic correlation only between myopia and disc area (genetic correlation [RhoG] = -0.12, P = 1.8 × 10-3), supporting the findings of the PRS approach. Conclusions:Using two complementary approaches we found no evidence to support a genetic overlap between myopia and POAG; our results suggest that the comorbidity of these diseases is not influenced by common variants. The association between myopia and optic disc size is well known and validates this methodology.